Ecological Services Analysis: Some Evidences and Policy Implications for Socio- Economic Development of Ecosystems of Việt Trì City, Phú Thọ Province - Phan, Trang Thị Kiều; Đoàn, Mai Hương (VNU Journal of Science: Natural Sciences and Technology; Vol 31 No 1, 2015)
Việt Trì is the capital city of Phú Thọ province, a tourism city known as the city of Vietnam is national origin. Besides, Việt Trì is also one of 12 “type I” cities in Vietnam with a high socio-economic development rate. Accordingly, the analysis of ecological services of the ecosystems of Việt Trì city is necessary for substainable socio-economic development. In this research, different ecosystems of Việt Trì city were studied based on already established understanding of Việt Trì ecology. After that, the important level of ecological services was analyzed and evaluated so as to propose orientations and methods for sustainable development. Keywords: Ecosystem, ecological services, sustainable development.